Parametric and design optimization investigation of a wavy fin and tube air heat exchanger using the T-G technique - Kumar V.; Sahoo R.R. (My University, 2025)
The focus of this paper is to optimize the air-side performance of a wavy fin and tube heat exchanger at different design parameters on an individual target response using the Taguchi method. However, a statistical concept, gray relational analysis, is also studied for combined optimization, considering all target responses at a time. Based on the heat exchanger requirement, parametric study for the air-side is regarded as a more significant heat transfer and lower frictional factor. Experimental correlations were available and used for the 27 orthogonal runs. Investigation revealed the highest 47.06% fin pitch, 37.24% fin pitch, 25.46% air velocity, and 23.9% fin thickness contribution ratio for the target response of friction factor (TPF), heat transfer coefficient, and Colburn factor, respectively, with the application of the Taguchi method in a heat exchanger. GRG gives an optimum set of design parameters, A3B3C2D1E3F2G1, for wavy fin and tube of fin pitch of 6 mm, tube row number of 6, waffle height 1.8 mm, fin thickness 0.12 mm, and air velocity 5 m/s. Also, longitudinal tube pitch is 27.5 mm, and transverse tube pitch of 24.8 mm, at which TPF is maximum while the friction factor is minimal. The Colburn factor is the most significant, minor friction factor, and the heat transfer coefficient and TPF are the most considerable in GRG. Hence, an improved heat transfer performance design of a wavy fin and tube heat exchanger is achieved using the above techniques. © 2022 Wiley Periodicals LLC.